PENGENALAN KULINER LOKAL "LAKSAMANA MENGAMUK" SEBAGAI UPAYA PELESTARIAN BUDAYA LOKAL DALAM KEGIATAN CAR FREE DAY - Zia Azzahra; Wardah Ibnatis Tsaniyah; Muhammad Ryza Hawary; Ferdi Riansyah; Alifa Marini Putri; Hesti Larasati; Andhini Pramudina; Nadine Novita Stephani Situmeang (Jurnal Padamu Negeri, 2025)
The traditional Riau Malay beverage, Laksamana Mengamuk, is a cultural heritage asset facing existential challenges amidst modernization. This study explores its potential as an educational tool in urban public settings. The research method involved direct public socialization at the Car Free Day on Jenderal Sudirman Street, Pekanbaru, featuring outreach, a making-of demonstration, and product sampling. The enthusiastic and positive public response indicates that a direct educational approach combined with a sensory (taste) experience is highly effective for building emotional and cultural connections to local culinary heritage. These findings confirm that direct sensory engagement is an effective method for enhancing cultural awareness. Therefore, strengthening collaboration among stakeholders is recommended for the sustainable preservation of local culinary heritage within public spaces.